Extreme modelling of missing Acacia Mangium height data - Adam, Mohd Bakri; Norazman, N.; Mohamad Kasim, Mohamad Roslan (Penerbit UTM Press, 2018)
Logging activity is one of the most important activities for tropical countries including Malaysia, as it produces quality trees for papers. One of the important tree species is the Acacia Mangium which it produces a soft tree for papermaking enterprises. The papers are exported to Europe and countries which have high demand for paper due to the rapid development of the printing industry. Thus we analyzed the height for individual trees. We investigate the maximum height of the trees from 1990 to 2006 and we t the data using extreme value model. Some of the data are missing and three imputation methods we used to solve this problem.